1956
DOI: 10.1109/aieepas.1956.4499306
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Equations for Analogue Studies of Synchronous Machines [includes discussion]

Abstract: Monseth and Robinson:' Ta = X2/27rfRa where Ra is defined as the armature resistance (not specifying a-c or d-c).3. McFarland:4 Ta = X/21rfRe where Re is the effective armature resistance and is defined as the ratio of the power per phase consumed in the armature to the square of the effective armature amperes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1956
1956
1972
1972

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The first simulates equation (3), which is the equation of the synchronous machine in the direct-axis. The second simulates equation (4), which is the equation of the machine in the quadratureaxis. Both give as its output the corresponding axis current and flux linkage.…”
Section: The Principle Of the Simulationmentioning
confidence: 99%
“…The first simulates equation (3), which is the equation of the synchronous machine in the direct-axis. The second simulates equation (4), which is the equation of the machine in the quadratureaxis. Both give as its output the corresponding axis current and flux linkage.…”
Section: The Principle Of the Simulationmentioning
confidence: 99%
“…Krause (68) developed this form further and Nandi (86) converted the representation to conform to proposed IEEE definitions (59) . Numerous other studies using analog computer representa tions are to be found in the literature (2,3,8,10,15,109).…”
Section: B Analog Computer Simulationmentioning
confidence: 99%